Lattice material infiltration for hybrid metal-composite joints: Manufacturing and static strenght. (1st August 2021) - Raimondi, Luca; Tomesani, Luca; Donati, Lorenzo; Zucchelli, Andrea
Abstract: An innovative technological solution for the manufacturing of high strength and high toughness metal-composite interface is here investigated, in which a 3DP printed cellular structure at the metal side is infiltrated by Advanced Sheet Molding Compound composite, in order to understand the effect of main geometric and processing parameters. Some hybrid metal-composite joints were produced, in which the effect of fiber orientation and cell dimension were considered as representative of the main processing issues. The outcome of the infiltration process was first checked on the hybrid joints, then samples were extracted for mechanical characterization of the bond, in comparison with cellular structure free joints.